Uso de farinha de inseto (Tenebrio molitor) como alimento alternativo para Apistogramma agassizii - Reis, Anna Cássia da Silva (Brasil, 2025)
Studies in the field of ornamental fish farming are increasingly expanding in the country, and in the Amazon region there are several species with potential for production. Among these is the Apistogramma agassizii, which needs more studies to determine its potential for captive breeding. The aim of this study was to assess the performance of this fish when fed different diets with levels of insect meal (Tenebrio molitor). The experiment was conducted in a completely randomized design, with 3 treatments and 4 replicates: T1: 100% commercial feed; T2: 50% commercial feed + 50% alternative feed; T3: 100% alternative feed. The results obtained were submitted to analysis of variance (ANOVA) at a significance level of 5%, with the assumptions of normality of the residuals being checked using the Tukey test. The results of the analysis of the physico-chemical parameters of the water in the treatments showed no significant difference. In relation to the zootechnical performance parameters of juvenile A. agassizii fed different levels of Tenébrio molitor meal, there were no significant differences for the conditions tested in this experiment, for all the indices evaluated.